Resiliensi sebagai bentuk pertahanan kesehatan mental pada survivor COVID-19: Resilience as a form of mental health defense in COVID-19 survivors - Nuqul, Fathul Lubabin; Fuaturosida, Rika; Fuady, Muh Anwar; Agung, Yusuf Ratu; Zuliani, Siti (Mediapsi, 2023)
COVID-19 pandemic that has occurred since 2020 worldwide has attracted attention because of its impact on all aspects of life. Mentality studies are important to support resilience for COVID-19 survivors and society in general. This study aims to explore the experiences and potentials of COVID-19 survivors. This study uses a phenomenological approach with Interpretative Phenomenological Analysis (IPA), data collection methods using semi-structured interviews. This study involved four respondents who conducted in-depth interviews. The purpose of this study was to reveal the initial reaction in COVID-19 survivors, to identify sources of resilience and protective factors and risk factors, as well as changes in the subject's behavior. The results show fear in COVID-19 survivors in the early stages of diagnosis. Survivors of COVID-19 can make decisions and solve problems well when they get social support from people around them and can optimize their spirituality